CONSUMER PROTECTION AGAINST COUNTERFEIT MOTORCYCLE OIL PRODUCTS FROM THE MAQASID SYARIAH PERSPECTIVE (CASE STUDY OF A WORKSHOP IN MEDAN AREA DISTRICT) - Hasbi Syadiki; Annisa Sativa (Program Pascasarjana UIN Sumatera Utara, 2025)
The circulation of counterfeit oil harms consumers because it reduces the quality of engine performance, increases the risk of vehicle damage, and jeopardizes user safety. The main factors influencing this phenomenon are low consumer awareness, weak supervision, and economic benefits for business actors. This study aims to examine consumer protection against the circulation of counterfeit oil in Medan Area Sub-district workshops from the Maqasid Syariah perspective, identify the factors causing it, and evaluate the effectiveness of consumer protection regulations. The method used is empirical juridical with a qualitative descriptive approach to describe consumer protection against counterfeit oil in practice. The results showed that the circulation of counterfeit oil contradicts the Maqasid Syariah principles, especially Hifz al-Mal (protection of wealth) because it causes financial losses, and Hifz an-Nafs (protection of life) because it increases the risk of accidents. Although consumer protection regulations already exist, supervision is still weak so that the circulation of counterfeit oil remains rampant. Therefore, more optimal law enforcement and increased consumer awareness are needed to be more selective in choosing the motorcycle oil products used.